Comparing Acute Effects of a Nano-TiO2 Pigment on Cosmopolitan Freshwater Phototrophic Microbes Using High-Throughput Screening. - Chu Thi Thanh Binh; Christopher G Peterson; Tiezheng Tong; Kimberly A Gray; Jean-François Gaillard; John J Kelly (PLoS ONE, 2015)
Production of titanium-dioxide nanomaterials (nano-TiO2) is increasing, leading to potential risks associated with unintended release of these materials into aquatic ecosystems. We investigated the acute effects of nano-TiO2 on metabolic activity and viability of algae and cyanobacteria using high-throughput screening. The responses of three diatoms (Surirella angusta, Cocconeis placentula, Achnanthidium lanceolatum), one green alga (Scenedesmus quadricauda), and three cyanobacteria (Microcystis aeruginosa, Gloeocapsa sp., Synechococcus cedrorum) to short-term exposure (15 to 60 min) to a common nano-TiO2 pigment (PW6; average crystallite size 81.5 nm) with simulated solar illumination were assessed. Five concentrations of nano-TiO2 (0.5, 2.5, 5, 10, and 25 mg L-1) were tested and a fluorescent reporter (fluorescein diacetate) was used to assess metabolic activity. Algae were sensitive to nano-TiO2, with all showing decreased metabolic activity after 30-min exposure to the lowest tested concentration. Microscopic observation of algae revealed increased abundance of dead cells with nano-TiO2 exposure. Cyanobacteria were less sensitive to nano-TiO2 than algae, with Gloeocapsa showing no significant decrease in activity with nano-TiO2 exposure and Synechococcus showing an increase in activity. These results suggest that nanomaterial contamination has the potential to alter the distribution of phototrophic microbial taxa within freshwater ecosystems. The higher resistance of cyanobacteria could have significant implications as cyanobacteria represent a less nutritious food source for higher trophic levels and some cyanobacteria can produce toxins and contribute to harmful algal blooms.